Evaluasi Program Pelatihan Kompetensi Penyuluh Pertanian Lapangan (PPL) Tingkat Kecamatan (Kasus Kecamatan Kerambitan, Marga, dan Selemadeg Barat Kabupaten Tabanan, Provinsi Bali) - MINIUS KOMBA; NI WAYAN SRI ASTITI; I GEDE SETIAWAN ADI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
The Evaluation of the Training Program in Competencies of the Agricultural FieldElucidators in the District Level (the Cases Taking Place at Kerambitan District, Marga, and West Selemadeg District, Tabanan Regency, Bali Province)The development of the ability of an Agricultural Field Elucidator ‘Penyuluh Pertanian Lapangan (PPL)’ plays a highly important role in the transformation of the accurate andefficient agricultural technological innovation. This current study was intended toidentify the level of the knowledge and ability which the PPLs have after joining thetraining program which was held to improve their competencies, and to identify theobstructions faced when joining the program. The respondents totaled 30 determinedusing the saturated sampling technique. The data were analyzed using the descriptivequalitative method. The results of the study showed that after joining the trainingprogram, the competencies they had were good enough or fine and the score achievedwas 3.00. The obstructions they faced were limited funds, time, labor and facilities.Apart from that, the perception which BPTP had was different from that which PPL andthe other related parties had; as a result, the program was not in accordance with whathad been expected for.Based on the result of the evaluation, it is suggested that the related parties should pay more attention to the funds, time and facilities used. Inaddition, the coordination between BPTP and PPL and the other related parties shouldbe improved to make the result achieved from the program in accordance with what hadbeen expected.